2016
DOI: 10.1002/nau.22965
|View full text |Cite
|
Sign up to set email alerts
|

l‐Theanine inhibits proinflammatory PKC/ERK/ICAM‐1/IL‐33 signaling, apoptosis, and autophagy formation in substance P‐induced hyperactive bladder in rats

Abstract: In conclusion, l-theanine through antioxidant and anti-inflammatory actions ameliorates SP-induced bladder hyperactivity via the inhibition of proinflammatory PKC/ERK/NF-κB/ICAM-1/IL-33 signaling, oxidative stress, bladder nerve hyperactivity, apoptosis, and autophagy. Neurourol. Urodynam. 36:297-307, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…L-theanine, namely N-ethyl-γ-glutamine, is a unique non-protein amino acid in tea [ 8 ] that can be degraded by glutaminase to glutamate and ethylamine in vivo [ 9 ]. It has many physiological functions, such as anti-oxidative stress [ 10 ], regulating immune response [ 11 ], and relaxing neural tension [ 12 ]. L-theanine alone or in combination with L-cystine administration can restore reduced glutathione (GSH) synthesis in mammals [ 13 ], further enhancing the antioxidant capacity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…L-theanine, namely N-ethyl-γ-glutamine, is a unique non-protein amino acid in tea [ 8 ] that can be degraded by glutaminase to glutamate and ethylamine in vivo [ 9 ]. It has many physiological functions, such as anti-oxidative stress [ 10 ], regulating immune response [ 11 ], and relaxing neural tension [ 12 ]. L-theanine alone or in combination with L-cystine administration can restore reduced glutathione (GSH) synthesis in mammals [ 13 ], further enhancing the antioxidant capacity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-33 as an alarmin was widely discussed about its functions in several different types of autoimmune diseases [ 19 , 20 ]. Some researches show that IL-33 was a proinflammatory factor [ 16 , 21 ], while others prove that it provokes a remedy mechanism [ 22 24 ]. In our study, we first explored how rIL-33 affects immune cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher levels of oxidative stress and apoptosis were observed in the pelvic ischemia group, which showed detrusor hyperactivity [29]. Tsai et al [30] also showed increased levels of oxidative stress, proinflammatory PKC/ERK/NF-κB/ICAM-1/IL-33 signaling, and apoptosis in OAB rats induced by substance P.…”
Section: Injmentioning
confidence: 92%